2006
DOI: 10.1128/aac.50.5.1859-1860.2006
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-Artemisinin Combination Therapy for Malaria

Abstract: Artemisinin and curcumin show an additive interaction in killing Plasmodium falciparum in culture. In vivo, 3 oral doses of curcumin following a single injection of ␣,␤-arteether to Plasmodium berghei-infected mice are able to prevent recrudescence due to ␣,␤-arteether monotherapy and ensure almost 100% survival of the animals.Artemisinin derivative-based combination therapy (ACT) has been advocated as the therapy of choice to handle widespread drug resistance in Plasmodium falciparum malaria, at the same time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
102
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(106 citation statements)
references
References 14 publications
3
102
0
1
Order By: Relevance
“…This can occur when the chemicals have similar modes of action, such that adding a second compound has the same effect as adding more of the first compound (Greco, Bravo, & Parsons, 1995), or when the two compounds target independent processes that have minimal effects on one another (Tallarida, 2000). A clinical example of additive effects due to independent actions would be the activities of two phytochemicals, artemisinin and curcumin, against malaria (Nandakumar, Nagaraj, Vathsala, Rangarajan, & Padmanaban, 2006). Artemisinin interferes with mitochondrial function (Krishna, Woodrow, Staines, Haynes, & Mercereau‐Puijalon, 2006), while curcumin causes DNA damage (Cui, Miao, & Cui, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This can occur when the chemicals have similar modes of action, such that adding a second compound has the same effect as adding more of the first compound (Greco, Bravo, & Parsons, 1995), or when the two compounds target independent processes that have minimal effects on one another (Tallarida, 2000). A clinical example of additive effects due to independent actions would be the activities of two phytochemicals, artemisinin and curcumin, against malaria (Nandakumar, Nagaraj, Vathsala, Rangarajan, & Padmanaban, 2006). Artemisinin interferes with mitochondrial function (Krishna, Woodrow, Staines, Haynes, & Mercereau‐Puijalon, 2006), while curcumin causes DNA damage (Cui, Miao, & Cui, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although curcumin itself displays only modest antimalarial activity, it was suggested that curcumin potentiates the action of the antimalarial a,b-arteether (Nandakumar et al, 2006). This was later shown to be due to immunomodulation by curcumin rather than a direct effect of the compound on the Plasmodium berghei parasites (Vathsala et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, proper utilization of currently existing drugs and enhancing the therapeutic efficiency of these drugs are of prime importance. In this stair, combination therapy is preferred over monotherapy for malaria treatment; and among various combination therapies, artemisinin-based combination therapy is the most preferred one (Nandakumar et al, 2006). Artemisininbased combination therapy mainly involves the partnering of two antimalarial drugs with distinct site of action or mode of action.…”
Section: Introductionmentioning
confidence: 99%